Human Target Attainment Probabilities for Delafloxacin against Escherichia coli and Pseudomonas aeruginosa - Hoover, Randall (Open Forum Infect Dis, 2017)
BACKGROUND: Delafloxacin (DLX) is a broad-spectrum fluoroquinolone antibiotic under FDA review for the treatment of ABSSSI. Previous studies determined DLX bacterial stasis and 1-log(10) bacterial reduction free AUC(0-24) / MIC (fAUC(0-24)/MIC) targets for Escherichia coli (EC) and Pseudomonas aeruginosa (PA) in a mouse thigh infection model. The resulting PK/PD targets were used to predict DLX target attainment probabilities (TAP) in humans. METHODS: Monte Carlo simulations were used to estimate TAP with DLX 300 mg IV, q12hr. Human DLX plasma pharmacokinetics were determined in patients with ABSSSI in a Phase 3 clinical trial. Individual AUC values were analyzed and determined to be log-normally distributed. The parameters of the AUC distribution were used to simulate random values for fAUC(24), which then were combined with random MIC values based on 2014–2015 US distributions of skin and soft tissue isolates of EC (n = 108) and PA (n = 40), to calculate PK/PD TAPs. RESULTS: DLX fAUC(0-24)/MIC targets for bacterial stasis and 1-log(10) bacterial reduction for EC were 14.5 and 26.2, and for PA were 3.81 and 5.02, respectively. The Monte Carlo simulations for EC predicted TAPs of 98.7% for stasis at an MIC of 0.25 μg/mL, and 99.3% for 1-log(10) bacterial reduction at an MIC of 0.12 μg/mL. The simulations for PA predicted TAPs of 97.3% for stasis and 86.5% for 1-log(10) bacterial reduction at an MIC of 1 μg/mL. CONCLUSION: DLX 300 mg IV, q12hr, should achieve fAUC24/MIC ratios that are adequate to treat ABSSSI caused by most contemporary isolates of EC and PA. For EC, isolates with DLX MICs ≤0.25 μg/mL comprised 73% of all isolates. For PA, isolates with DLX MICs ≤1 μg/mL comprised 88% of all isolates. Similar results would be expected for TAP with oral DLX 450 mg, q12hr. DISCLOSURES: R. Hoover, Melinta Therapeutics: Consultant, Consulting fee; A. Marra, Melinta Therapeutics: Employee, Salary; E. Duffy, Melinta Therapeutics: Employee, Salary; S. K. Cammarata, Melinta Therapeutics: Employee, Salary